2018
DOI: 10.1002/ijc.31607
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitory antibody targeting carbonic anhydrase XII abrogates chemoresistance and significantly reduces lung metastases in an orthotopic breast cancer model in vivo

Abstract: Carbonic anhydrase XII (CAXII) is a membrane-tethered ectoenzyme involved in intracellular pH regulation and overexpressed across various types of human cancer. Because CAXII inhibition shows antitumor activity in vitro, it is thought that the enzyme is mandatory for maximum tumor growth, above all under hypoxic conditions. Recently, it has been shown that CAXII is co-expressed along with the P-glycoprotein (P-GP) on many tumor cells and that both proteins physically interact. Of interest, blocking CAXII activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 29 publications
(74 reference statements)
1
37
0
1
Order By: Relevance
“…A recent study had demonstrated that CA XII inhibitor abrogates chemoresistance and significantly reduces lung metastases in in vivo breast cancer model. 35 A similar CA XII inhibition by 215900 might have contributed to the inhibitory effects observed in this study. Further studies are required to characterize 215900-mediated CA XII inhibition and to elucidate the role of CA XII in human osteosarcoma.…”
Section: Discussionsupporting
confidence: 52%
“…A recent study had demonstrated that CA XII inhibitor abrogates chemoresistance and significantly reduces lung metastases in in vivo breast cancer model. 35 A similar CA XII inhibition by 215900 might have contributed to the inhibitory effects observed in this study. Further studies are required to characterize 215900-mediated CA XII inhibition and to elucidate the role of CA XII in human osteosarcoma.…”
Section: Discussionsupporting
confidence: 52%
“…Focusing on a clinically relevant tumor model, we transplanted human MDA-MB-231 mammary carcinoma cells, expressing mCherry and firefly luciferase, into the mammary fat pad of NOD scid gamma (NSG) mice and allowed the tumors to grow and metastasize for 6-10 weeks (Figure 1A) [18][19][20] . Furthermore, we injected the fluorescently-tagged 6A10 therapeutic antibody that has been shown to reduce tumor burden in this model 19,20 . To investigate cancer metastasis and therapeutic antibody targeting in whole mouse bodies at the single cell level, we developed DeepMACT.…”
Section: Resultsmentioning
confidence: 99%
“…However, so far there has been no methodology to determine the distribution of therapeutic antibodies in the entire body at cellular resolution. Here, we used DeepMACT to assess biodistribution of the therapeutic monoclonal antibody 6A10 directed against human carbonic anhydrase XII (CA12) 19,20,24 . CA12 is overexpressed in various types of cancers and blocking its activity with the antibody 6A10 reduces tumor growth 19 and increases the sensitivity of tumor to chemotherapy 20 .…”
Section: Deepmact Reveals Therapeutic Antibody Targeting At the Cellumentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering lung BABB clearing was reported by Scott et al., who presented the first detailed view on the relationship between nerves, vessels and airways architecture, detected novel patterns of pleural innervations and connectivity patterns of pleural nerves. Solvent‐based clearing proved also beneficial for the detection and analysis of lung tumor metastases …”
Section: Application Of Toc For Particular Peripheral Organsmentioning
confidence: 99%